The correlation of sacral table angle to spinopelvic sagittal alignment in healthy adults - Nan Ru; Keith D. K. Luk; Jianmin Sun; Guodong Wang (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background The sacrum plays an important role in sagittal balance of the spine, whereas the exact association between sacral parameters, specifically the sacral table angle (STA) and spinopelvic parameters has been only scarcely assessed. It aims to investigate the correlations between the sacral parameters and spinopelvic sagittal alignment parameters in healthy adults. Methods A cohort of 142 Northern Chinese healthy adults between 18 and 45 years old were recruited between April 2019 and March 2021. Full-spine standing X-ray films were performed for every volunteer. The sacral parameters were measured: sacral table angle (STA), sacral inclination (SI) and sacral slope (SS). The spinopelvic sagittal alignment parameters included: pelvic incidence (PI), pelvic tilt (PT), lumbar lordosis (LL), thoracic kyphosis and the apex of lumbar lordosis (LLA). The correlations analysis, as well as the linear regression analysis, were performed between STA, SI and the spinopelvic parameters. Results An equation ‘STA = SI + 90 − SS’ was revealed to represent the interrelationships between STA, SI and SS. STA was statistically correlated with PI (r s  = − 0.693), PT (r s  = − 0.342), SS (r s  = − 0.530), LL (r s  = 0.454), and LLA (r s  = 0.438). SI correlated with STA (r s  = 0.329), PT (r s  =  − 0.562), SS (r s  =  − 0.612) and LL (r s  = 0.476). Simple linear regression analysis also verified the correlation between STA and PI (y = − 1.047x + 149.4), SS (y = − 0.631x + 96.9), LL (y = 0.660x − 117.7), LLA (y = 0.032x + 0.535), and SI (y = 0.359x + 8.23). Conclusion The equation ‘STA = SI + 90 − SS’ indicates the exact geometric relationship between STA, SI and SS. The sacral parameters, both STA and SI, correlate to the spinopelvic sagittal alignment parameters in healthy adults. The linear regression analysis results also give predictive models for spinopelvic sagittal alignment parameters based on the invariant parameter STA, which are helpful for surgeons in designing an ideal therapeutic plan.